Pengaruh Solvabilitas dan Profitabilitas terhadap Audit Delay pada Perusahaan BUMN Periode 2019-2023 - Rachmawati, Rica; Nurhasanah, Nunung; Nadeak, Banuara (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This quantitative research aims to determine the factors that influence audit delay, namely solvency and profitability in BUMN listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period with a population of 55 observations. Meanwhile, the sample that met the criteria was 24 observations. The data collection technique was carried out using secondary data from annual reports of state-owned companies during the observation period. The research instrument uses debt to asset ratio (DAR) as a proxy for solvency and return on assets (RoA) as a proxy for profitability, and audit delay data. Data analysis was carried out using multiple linear regression. The results of this research reveal that simultaneously there is a significant influence between the solvency and profitability ratios on audit delay in state-owned companies in Indonesia during the 2019-2023 period. However, partially there is a significant treatment in the opposite direction of the two ratios; The solvency ratio has a negative effect, while the profitability ratio has a positive effect on audit delay.